Tourist perception on tourism sustainability dimensions of Melaka, Malaysia - Mahat, Norsyafina (2016)
Sustainable tourism refers to the ways of managing environment, protecting the environment and socio-cultural capital, measuring acquired self-sufficiency, and the factor that influences the needs of present and future generation’s satisfaction.However, few researchers have focused on tourists’ view towards sustainable tourism.Therefore, the main purpose of this research is to examine tourists’ perceptions on sustainable tourism dimensions, namely environment, economy, social, authenticity and service delivery and their relationships toward overall tourists’ satisfaction.Questionnaires were developed and this study was undertaken in Melaka. Melaka is known as a historical city and was recognized as the World Heritage Site (WHS), by UNESCO since 2008. Besides, Melaka was amongst the top most visited state in Malaysia, comprising of both domestic and international tourists (Tourism Melaka,2014). A total of 400 respondents were participating in this research. There were five main dimensions of sustainable tourism which were represented by 30 item scales. The dimensions were environment, economy, social, authenticity, and service delivery and these were referred as the indicators for Sustainable Attraction Management (SAM).The relationship between SAM and tourists’ satisfaction was also examined. The sustainable tourism dimensions were tested for its reliability strength and the results showed that all dimensions were highly reliable. Descriptive statistic which involved frequency distribution was used to achieve the first objective which was to analyze tourists’ awareness towards sustainable tourism dimensions in tourist attraction. The results showed that the respondents were most aware of the 1st rank as in economy initiative due to the highest mean score. Then followed by authenticity(2nd rank), social (3rd rank), service delivery (4th rank), and the last rank was due to the environment. A conceptual model of the study with six hypotheses was developed in this research.Multiple Regressions were used to achieve the second objective which was to examine the sustainable tourism dimensions in influencing the overall tourists’satisfaction.Regression results showed that the environment initiative did not influence on the overall satisfaction among the tourists. However, other four sustainable tourism dimensions; economy, social, authentic and service delivery gained a significant result and influenced the overall satisfaction of the tourists. Results also showed a significant positive relationship between tourists’ satisfaction and revisit intention. Hence, this research provides support for sustainable tourism concept which signifies tourism to have the characteristics to improve the quality of life of host community, to provide quality experience to the visitors, and to maintain social quality for the use of both tourists and the host community (WTO 1993).The findings contributed to a bigger perspective in developing the tourism industry in the country, particularly in making attractions, sustainable in terms of environment,economy, social, authenticity, and service delivery dimension. More importantly, this research provides evidence on useful scales in measuring sustainable tourism for tourists’ attraction and the scales are viewed as the indicators for Sustainable Attraction Management (SAM).